Impact of hygiene promotion intervention on acute childhood diarrhea: evidence from a cluster-randomized trial in refugee communities in Gambella Region, Ethiopia - Getachew Kabew Mekonnen; Bezatu Mengistie Alemu; Geremew Sahilu Gebrie; Helmut Kloos; Worku Mulat Legesse (Journal of Water, Sanitation and Hygiene for Development, 2023)
Background: Diarrheal illnesses are mainly linked with poverty, and hygiene promotion programs can significantly reduce childhood diarrhea when interventions are tested in stable communities. However, there is no sufficient evidence in emergency context. Methods: A cluster-randomized controlled trial was conducted in Teirkidi and Pugnido refugee camps. Intention to treat was applied in analyses of the results of this trial. Logistic, poison regression and generalized estimating equation (GEE) models were used to evaluate changes in cluster-level hygiene behaviors and period prevalence and incidence of diarrhea with its confidence intervals (95% CI) and p < 0.05 significant cutoff point. Results: The reported diarrhea episodes were 1,307 (15.6 episodes per 100 person-weeks observation) among the intervention households and 1,619 (18.9 episodes per 100 person-weeks observation) in the control households. Under-five children living in households that received hygiene promotion had a 15% [p < 0.001; adjusted IRR: 0.85, 95% CI: 0.79 0.92] and a lower incidence of diarrhea compared with children living in control households. Conclusion: The study confirms that hygiene promotion intervention significantly reduces the incidence rate of childhood diarrhea in refugee camps. Hence, gains in the reduction of childhood diarrhea can be achieved in refugee camps through an enhanced hygiene promotion program. HIGHLIGHTS My research could evaluate the burden of childhood diarrheal diseases and try to address the problem in the refugee context.; Reducing childhood diarrhea burden.;